الزواج عبر مواقع التواصل الإجتماعي (فيسبوك انموذجا) دراسة ميدانية على عينة من شباب ولاية توقرت - نجاة خروبي; صبرينة خبيش (جامعة الوادي - University of Eloued, 2025)
"تهدف الدراسة إلى التعرف على التغيرات التي دفعت بالشباب للجوء إلى الزواج عبر فيسبوك،وقد انطلقنا من الإشكال التالي: ما هي المتغيرات الاجتماعية التي تدفع بالشباب للجوء إلى الزواج عبر فيسبوك واندرجت تحتها التساؤلات الفرعية هل العوامل الاجتماعية تدفع بالشباب للجوء إلى الزواج عبر فيسبوك ؟ هل العوامل الثقافية تدفع بالشباب للجوء إلى الزواج عبر فيسبوك ؟ وكانت الإجابة على ذلك بالفرضيات التالية : العوامل الاجتماعية تدفع بالشباب للجوء إلى الزواج عبر فيسبوك العوامل الثقافية تدفع بالشباب للجوء إلى الزواج عبر فيسبوك حيث تمثل منهج الدراسة في المنهج الوصفي التحليلي لأنه الأنسب في هذه الدراسة لمعرفة واقع الدراسة وجوانبها ووصفها وتحليلها ،وكانت طريقة اختيار العينة عشوائية حيث تم توزيع 150استمارة ،وتم استرجاع 100استمارة فيما لم ترجع 35استمارة وتم إلغاء 15استمارة من الدين لا يستخدمون فيسبوك ،أي كانت عدد الاستمارات المدروسة 100،وتم توزيعها على شباب في إحياء بلدية تماسين ولاية توقرت ،وقد توصلت هد الدراسة أنه هناك عوامل أي تغيرات اجتماعية تدفع بالشباب للجوء إلى الزواج عبر المواقع التواصل الاجتماعي فيسبوك. "The study aims to identify the changes that have led young people to resort to marriage through social media platforms, particularly Facebook. To achieve this objective, we began with the following main research question: What are the social variables that drive young people to seek marriage through Facebook? This overarching question gave rise to the following sub-questions: Do social factors drive young people to seek marriage through Facebook? Do cultural factors influence young people to resort to marriage through Facebook? The answers to these questions were formulated as the following hypotheses: Social factors drive young people to seek marriage through Facebook. Cultural factors influence young people to resort to marriage through Facebook. The study adopted a descriptive-analytical methodology, as it is the most suitable for understanding and analyzing the reality and dimensions of the phenomenon under investigation. The sample was chosen randomly, with 150 questionnaires distributed. Of these, 100 were retrieved, while 35 were not returned and 15 were excluded because the respondents did not use Facebook. Thus, the study was based on 100 valid questionnaires, which were distributed among young people in neighborhoods of the Témacine municipality in Touggourt Province. The study concluded that there are indeed social changes and factors that drive young people to resort to marriage through social media platforms, especially Facebook.
مذكرة ماستر قسم علوم الاجتماعية تخصص علم اجتماع الاتصال.
Keywords: الشباب; الإرتباط; المواقع التواصل الاجتماع; الزواج; فيسبوك; Facebook; Marriage; Social Medi، Engagement،Youth